The role of reciprocation in social network formation, with an application to blogging - Alexia Gaudeul; Caterina Giannetti (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
This paper deals with the role of reciprocation in the formation of individuals' social networks, that is to what extent initiating a relation brings about its reciprocation. Following the activity of a panel of bloggers over more than a year, we seek to establish whether bloggers are mainly involved in social networking or are part of the media industry. We adapt a standard capital investment model to study the effect of reciprocation on the building of social capital. Results of our analysis confirm that activity and reciprocation both play a role in the dynamics of social media.
Keywords: C33; D85; L82; 330; bloggers; friendship; livejournal; media; panel data; reciprocation; reciprocity; social capital; social media; social networks; Virtuelle Gemeinschaft; Austauschtheorie (Soziologie); Online-Netzwerk; Social Capital